PERSEBARAN APARTEMEN DI WILAYAH BERDAMPAK PERUBAHAN IKLIM - Syarifah Syaukat; Muhammad Nur Kamaludin (Jurnal Kajian Pengembangan Perkotaan, 2012)
The growth of properties in Jakarta continues to increase especially apartments, shopping centers and office buildings with occupancy rates above 80%. The issue of climate change becomes an important part of the distribution of apartments as residential buildings, especially in North Jakarta. Using the method of Geographical Information Systems (GIS), this study identified the distribution of apartments at 36 points within three locations, namely Penjaringan Village, Pademangan Village, and Cilincing Village. The result of this study indicates the presence of areas which are vulnerable and quite prone to flood inundation. Furthermore, this result could help create an innovative urban plan with mitigation strategies.